A prospective open‐label trial of a CBD/THC cannabis oil in dravet syndrome. Issue 9 (1st August 2018) - McCoy, Bláthnaid; Wang, Laura; Zak, Maria; Al‐Mehmadi, Sameer; Kabir, Nadia; Alhadid, Kenda; McDonald, Kyla; Zhang, Grace; Sharma, Rohit; Whitney, Robyn; Sinopoli, Katia; Snead, O. Carter
Abstract: Introduction: Both Δ 9 Tetrahydrocannabidiol (THC) and cannabidiol (CBD) components of cannabis, have been shown to have anticonvulsant effects. Cannabis oils are used to treat seizures in drug‐resistant epilepsy (DRE). Recent trials provide data on dosing, side effects, and efficacy of CBD, yet there is a paucity of information on THC in epilepsy. Primary objective was to establish dosing and tolerability of TIL‐TC150 ‐ a cannabis plant extract produced by Tilray ®, containing 100 mg/mL CBD and 2 mg/mL THC‐ in children with Dravet syndrome. Secondary objectives were to assess impact of therapy on seizures, electroencephalogram (EEG) and quality of life. Methods: Twenty children received add‐on therapy with TIL‐TC150. The dose ranged from 2 to 16 mg/kg/day of CBD and 0.04 to 0.32 mg/kg/day of THC. Patients were monitored for tolerability and adverse events, and secondary objectives. Results: Nineteen participants completed the 20‐week intervention. Mean dose achieved was 13.3 mg/kg/day of CBD (range 7–16 mg/kg/day) and 0.27 mg/kg/day of THC (range 0.14–0.32 mg/kg/day). Adverse events, common during titration included somnolence, anorexia, and diarrhea. Abnormalities of liver transaminases and platelets were observed with concomitant valproic acid therapy. There was a statistically significant improvement in quality of life, reduction in EEG spike activity, and median motor seizure reduction of 70.6%, with 50% responder rate of 63%. Conclusions: TIL‐TC150 was safe and well tolerated in our subjects. TIL‐TC150 treatment resulted in a reduction in seizure counts, spike index on EEG, and improved quality of life measures. This study provides safety and dosing information for THC‐containing cannabinoid preparations.